Reconstruction of Ecotourism Resources Based on Sharia Tourism - Agung Respati; Muh. Nashirudin (Al Mashaadir : Jurnal Ilmu Syariah, 2025)
This study aims to: analyze the impact of the Grojogan Sewu Nature Tourism Park (TWA) ecotourism development on community income, employment and business opportunities, and land use within the surrounding community; and analyze the development of ecotourism resources from a sharia tourism perspective. This study is a survey conducted around the Grojogan Sewu Nature Tourism Park tourist attraction located in Tawangmangu District, Karanganyar Regency. The results indicate that ecotourism development impacts community income, employment and business opportunities, and land use in the study area. Ecotourism development has a positive impact on community income, employment and business opportunities, and land use. The reconstruction of ecotourism resource development from a sharia tourism perspective has met the criteria for sharia tourism development, namely ecotourism resource development from a sharia tourism perspective, from an ecotourism perspective, from an environmental management system perspective, from a tourist destination competitiveness perspective, and from a perspective of preserving socio-cultural values ​​and local wisdom. The results of this study indicate that ecotourism development in the study area has met the criteria for developing ecotourism based on Sharia tourism.